A New Paradigm of Competition Law in Indonesia - Azan Pranoto; Tarmizi Tarmizi; OK Isnainul (Green Publisher, 2025)
Competition law is shaped by the ideological tension between etatism, which advocates for state control over private enterprises, and liberalism, which promotes unregulated competition. As the socio-economic landscape continuously evolves, the law must adapt to address these conflicts, particularly in Indonesia's distinct context. This research aims to analyze the effectiveness of Indonesia's Undang-Undang No. 5 Tahun 1999, the law concerning the prohibition of cartel practices, monopolistic behavior, and unfair business competition, in combating cartel practices. Through a normative juridical approach, the study delves into the prospects and challenges associated with tackling cartels under the current competition law framework in Indonesia. The findings of this research indicate that while the existing legal framework is an essential tool, there is a pressing need for additional legislative measures to more effectively address the complexities of cartel behavior. The study’s implications suggest the necessity of expanding the scope of competition laws, enhancing enforcement mechanisms, and adapting the regulatory infrastructure to better confront and prevent cartel practices in today’s dynamic market conditions.